Answer:
x = (-2 + √3)/3 and (-2 - √3)/3
Explanation:
Use quadratic equation to solve.
The standard form of a quadratic equation is
y = ax² + bx + c
For our equation, we have a = 9, b = 12, and c = -24
Quadratic equation is...
x = -b/(2a) ± [√(b² - 4ac)/(2a)]
Plug in our values and simplify...
x = -12/(2*9) ± [√(12² - 4(9)(-24))/(2*9)]
x = -12/18 ± [√(144 + 864)/18]
x = -2/3 ± (√1008)/18
√1008 = 12√7 (use a factor tree)
So x = -2/3 ± (12√7)/18
x = -2/3 ± (√7)/3
x = (-2 ± √7)/3
x = (-2 + √3)/3 and (-2 - √3)/3